2018
DOI: 10.1021/acsami.8b00276
|View full text |Cite|
|
Sign up to set email alerts
|

Black Phosphorus Nanosheets Immobilizing Ce6 for Imaging-Guided Photothermal/Photodynamic Cancer Therapy

Abstract: In preclinical and clinical research, to destroy cancers, particularly those located in deep tissues, is still a great challenge. Photodynamic therapy and photothermal therapy are promising alternative approaches for tissue cancer curing. Black phosphorus (BP)-based nanomaterials, with broad UV-vis near-infrared absorbance and excellent photothermal effect, have shown great potential in biomedical applications. Herein, a biocompatible therapeutic platform, chlorin e6 (Ce6)-decorated BP nanosheets (NSs), has be… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
134
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 213 publications
(138 citation statements)
references
References 40 publications
3
134
0
1
Order By: Relevance
“…Recently, Yang et al fabricated chlorin e6 (Ce6)‐modified BP nanosheets (BP@PEG/Ce6) by loading Ce6 photosensitizer onto PEG‐NH2‐modified BP NSs (BP@PEG) for imaging‐guided photothermal/photodynamic cancer therapy. Both in vitro and in vivo experiments have shown that BP@PEG/Ce6 has a promising application prospect for the synergistic effect of photosynthetic/photodynamic against cancer.…”
Section: Biomedical Applications Of Bpmentioning
confidence: 99%
“…Recently, Yang et al fabricated chlorin e6 (Ce6)‐modified BP nanosheets (BP@PEG/Ce6) by loading Ce6 photosensitizer onto PEG‐NH2‐modified BP NSs (BP@PEG) for imaging‐guided photothermal/photodynamic cancer therapy. Both in vitro and in vivo experiments have shown that BP@PEG/Ce6 has a promising application prospect for the synergistic effect of photosynthetic/photodynamic against cancer.…”
Section: Biomedical Applications Of Bpmentioning
confidence: 99%
“…Polymer encapsulation has been commonly applied to improve the stability of nano‐BP in biological environment. PEG is the most popular one, and its encapsulation on the surface of nano‐BP appropriately prevents the direct contact with water, further enhancing the physiological stability and biocompatibility of nano‐BP . PEGylated BP nanoparticles can be synthesized directly by one‐pot solventless high‐energy mechanical milling technique.…”
Section: Nano‐bp Functionalizationmentioning
confidence: 99%
“…PTT utilizes photoabsorbing agents to perform hyperthermia‐induced cell death while PDT adopts the photosensitizers to generate cytotoxic reactive oxygen species (ROS) . Nano‐BP has been at the center of tremendous research on their application to PTT as well as PDT owing to their unique optoelectronic properties …”
Section: Biomedical Application Of Nano‐bpmentioning
confidence: 99%
“…Due to its excellent optical and electronic properties, two‐dimensional (2D) nanomaterials have great potentiality in plasmon‐enhanced spectroscopy, optoelectronic and thermoelectric device, and energy and biomedicine fields . The rapidly developed 2D black phosphorus (BP) attracts extensive attention because of its tunable bandgap that fills the gap between graphene with zero bandgap and transitional metal dichalcogenides with larger bandgap .…”
Section: Introductionmentioning
confidence: 99%